The Nonrelativistic Scattering States of the Deng-Fan Potential - Bentol Hoda Yazarloo; Liangliang Lu; Guanghui Liu; Saber Zarrinkamar; Hassan Hassanabadi (Advances in High Energy Physics)
The approximately analytical scattering state solution of the Schrodinger equation is obtained for the Deng-Fan potential by using an approximation scheme to the centrifugal term. Energy eigenvalues, normalized wave functions, and scattering phase shifts are calculated. We consider and verify two special cases: the l=0 and the s-wave Hulthén potential.